Radial Retinotomies with Endodiathermy for Severe Proliferative Vitreoretinopathy: Short-Term Results. (28th February 2016) - Jiang, Zhaoxin; Qiu, Suo; Lou, Bingsheng; Lin, Miaoli; Tan, Junlian; Lin, Xiaofeng
Abstract : Purpose. Retinal redetachment of silicone oil-filled eyes continues to be a frustrating condition that typically requires retinectomy. We proposed radial retinotomy as a potentially less invasive surgery. Here, we preliminarily explored its feasibility, efficacy, and safety. Methods. Totally 9 eyes of 9 consecutive patients were included in a prospective noncomparative trial. A series of retinotomies were created by endodiathermy in a radial pattern to relax the foreshortened retina. The eye was refilled with fresh silicone oil. The treated eyes were examined via visual acuity (VA) tests, tonometry, slit-lamp microscopy, and fundus photography during a 6-month observation period. Results. The procedure was completed in an average of 28 minutes from silicone oil removal to fresh silicone oil placement. Fundus photography demonstrated that 7 of the 9 eyes (78%) exhibited retinal reattachment. On average, VA was significantly improved within the first 2 weeks (P = 0.02 ) and remained stable for the following 6 months. The change in intraocular pressure was not significant (P = 0.76 ), and no adverse event was observed (0%). Conclusion. Radial retinotomies with endodiathermy were shown to be feasible, effective, and safe in selected cases of inferior contracted retina without vitreous base fibrosis over a 6-month observation period. This trial is registered withNCT02201706 .